The Efficiency of the Pharmaceutical Industry in Indonesia: A Stochastic Frontier Approach - Fitrah Minangsari; Bernadette Robiani; Mukhlis Mukhlis (Jurnal Ekonomi Pembangunan, 2019)
This study aims to analyze the efficiency of the pharmaceutical industry (ISIC code: 21012) in Indonesia. The data used in this study are secondary data from 2000 to 2015. The analysis technique used in this study is the Stochastic Frontier Approach. Based on the results of the analysis, it can be seen that the pharmaceutical industry in Indonesia of 2000-2015 in technically it has not Reached amount of 0.96455986 optimal efficiencies. The capital variable does not have a significant effect on the output produced by the producer in the pharmaceutical industry, while the labor variable has it.